Tobacco Use Decreases Visual Sensitivity in Schizophrenia - Fernandes, Thiago M. P.; Andrade, Michael J. Oliveira de; Santana, Jessica B.; Nogueira, Renata M. Toscano Barreto Lyra; Santos, Natanael A. dos (Frontiers in Psychology, 2018)
Smoking prevalence for patients diagnosed with schizophrenia (SCZ) is higher than in the general population. Chronic tobacco use in SCZ patients may reduce the side effects of antipsychotic drugs and act in a self-medicating way. Understanding how chronic tobacco use influences the visual sensitivity has clinical implications, and may serve as a potential non-invasive diagnosis for early-stage visual processing. In the present study, 40 smokers controls (SC), 20 SCZ tobacco users and 20 SCZ nonusers were recruited from the Psychosocial Care Center. All SCZ groups were firstly compared to SC. Our results suggested that patients with schizophrenia that are chronic tobacco use showed reduced visual sensitivity for chromatic (p < .001) and achromatic (p < .001) stimuli compared to all groups. To our knowledge, this is the first study evaluating effects of chronic tobacco use on visual sensitivity in SCZ patients. Our purpose was to provide new directions for future research, mainly psychophysical and electrophysiological studies. In addition, our study highlight the need to alert the observation of addictive behavior in patients with SCZ. The results obtained here target changes in public policies to improve the quality of life of SCZ patients and their families.